Efisiensi Biaya dengan Sistem PDCA Menggunakan Metode Quality control circle (QCC) di PT. XYZ Kabupaten Sidoarjo - Asiyah, Dewi; Amilia, Winda; Wiyono, Andi Eko; Suryaningrat, Ida Bagus; Wibowo, Yuli (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2022)
The rapidly increasing business world demands that every company has the ability to compete. The policy in order to keep the company's smoking stable is to control production costs. PT. XYZ is an international manufacturing company that produces chocolate powder with several production processes in it. The decline in sales that occurred in PT. XYZ resulted in decreased company costs. In this problem, it is necessary to make improvements for PT. XYZ in order to obtain a solution to stabilize the company's production costs. The method used in this study is Quality Control Circle (QCC) with the application of the PDCA system. The results showed that the purchase of 2 ply paper bag packaging (PB2PL) is one of the activities that affect production costs with the largest expenditure in PT. XYZ. The improvement made is by applying PB2PL reuse. PB2PL is packaging used to package semi-finished materials, so that PB2PL can be reused which will provide benefits in terms of cost. The target of purchasing PB2PL after repairs is from 9,818 pcs to 3,500 pcs per month. Analysis of potential cost efficiency obtained by the first reuse of RP.47,859,052 per month, the second reuse of IDR 38,708,676 per month and the third reuse of IDR 29,558,300 per month. Analysis of potential costs with the application of the target is Rp. 30,798,617 per month. Application of PB2PL reuse in PT. XYZ for two months provided a cost efficiency of Rp.96,891,759. So that the problem would not occur again in the future, standardization was made in the form of a Standard Operating Procedure (SOP) reuse PB2PL .